IS ACADEMIC FREEDOM IN BELGIUM AND THE NETHERLANDS UNDER DURESS? - Geuens, Maaike (Pravni zapisi, 2025)
Academic freedom is considered a cornerstone of democratic higher education, yet its institutional foundations are becoming increasingly fragile. This article examines how financial austerity and ideological contestation interact to reshape academic freedom. It argues that formal constitutional and supranational safeguards coexist with subtle but cumulative mechanisms of erosion, including performance-based funding, managerial governance, politicized scrutiny of specific disciplines, and transnational ideological interference. While Belgium and the Netherlands still perform comparatively well in Europe, the convergence of budgetary constraints and ideological polarization generates chilling effects, self-censorship and strategic compliance. The article concludes that academic freedom cannot be assumed to be secure by default. It calls for renewed safeguards, combined with institutional cultures and international alliances that strengthen the structural resilience of academic freedom.